Eigenvalues and bifurcation for elliptic equations with mixed Dirichlet-Neumann boundary conditions related to Caffarelli-Kohn-Nirenberg inequalities - Colorado, Eduardo; Peral, Irened (Topological Methods in Nonlinear Analysis, 2004)
This work deals with the analysis of eigenvalues, bifurcation and Hölder continuity of solutions to mixed problems like -(|x|^-pγ | abla u|^p-2 abla u) = f_λ(x,u) , &u > 0 in Ω , u = 0 & on Σ_1, |x|^-pγ| abla u|^p-2uu = 0 & on Σ_2, involving some potentials related with the Caffarelli-Kohn-Nirenberg inequalities, and with different kind of functions f_λ (x,u).